Subclinical Hypothyroidism as the Most Common Thyroid Dysfunction Status in Children With Down’s Syndrome - Szeliga, Kamila; Antosz, Aleksandra; Skrzynska, Karolina; Kalina-Faska, Barbara; Januszek-Trzciakowska, Aleksandra; Gawlik, Aneta (Frontiers in Endocrinology, 2022)
Introduction: Thyroid dysfunctions are one of the most common abnormalities co-existing in children with Down’s Syndrome (DS) and have been reported in up to 54% cases. Aim of the study: The purposes of this retrospective study were to investigate the course of subclinical hypothyroidism in children with DS, to evaluate the thyroid function of these subjects in relation to the risk of developing overt thyroid disease and autoimmunity, and to identify clinical and biochemical characteristics of patients prescribed L-T4 therapy in children and adolescents with DS and SH Material and methods: The records of DS patients referred to the Endocrinology Outpatient Clinic between 2010-2015 for screening of thyroid function were observed till the end of 2019 June and analyzed retrospectively. The children diagnosed with congenital hypothyroidism, acute lymphoblastic leukemia, seizures and treated with drugs that may have interfered with thyroid function like lithium, antiepileptic or iodinated drugs, and glucocorticoids were excluded from the study. Results: The data of 77 DS patients was collected, evaluated and analyzed. The study group consisted of 73 patients (32 girls and 41 boys with the mean age at baseline of 3.0 ± 4.5 years). 63/73 (87%) children were diagnosed with SH. The 16/63 (25.4%) patients were followed-up without the treatment (group SH-T0) and therapy with levothyroxine (L-T4) was introduced in 47/63 (74.6%) SH children with the mean dosage of 1.8 ± 1.0 μg/kg/day (group SH-T1). Thyroxine supplementation did not improve growth expressed as hSDS (0.1 ± 1.3, ranged -2.1 to 3.8 in SH-T0 vs. 0.0 ± 0.7, ranged -1.7 to 1.4 in SH-T1, p=0.96) and BMI Z-score (0.3 ± 0.9, ranged -0.9 to 2.6 in SH-T0 vs. 0.3 ± 1.1, ranged -2.1 to 2.9 in SH-T1, p=0.65). Positive anti-TPO and anti-TG antibodies were detected in 7/63 (11.1%) DS cases. Conclusions: SH is the most frequent presentation of thyroid gland dysfunction in DS children. A small percentage of patients develops an overt hypothyroidism, particularly in female gender with mostly positive titer of antithyroid autoantibodies.